Karakteristik Sifat Kimia Tanah Dan Kandungan Merkuri Pada Lahan Bekas Tambang Emas Dan Lahan Perkebunan Kelapa Sawit (Elaeis Guineensis Jacq.) - David Willy Saputra Manullang; Gusmini; Rezki, Dewi (Jurnal Riset Perkebunan, 2021)
The present study was conducted in Tebing Tinggi Village, Pulau Punjung Sub-district, Dharmasraya District was motivated by a desire to exploit land resources, especially open access land that was formerly a gold mine by cultivating oil palm plants. The objectives of this study were to determine the characteristics of soil chemical properties, the soil fertility level, and the level of mercury (Hg) contamination in former gold mining land by compared with the soil chemical fertility of oil palm plantations. The research method was a survey by purposive sampling. The Soil sampling for analysis of soil chemical properties was carried out by drilling of 0-40 cm deep with 12 sample points divided into 4 locations, where 3 locations in the former gold mine area that were grouped into three segments, namely segments 1, 2 and 3 and one location was in oil palm land. The parameters of soil chemical properties observed were pH, Al-dd, C-organic, C / N Ratio, N, P, K and Hg (Mercury). The results of this research, shows that the characteristics of soil chemical properties in the former gold mining area have decreased the level of soil fertility, characterized by the very low pH value and C-organic content, ​​so that the nutrients contained in the land are very limited when compared to the soil fertility in oil palm land. This is indicated by the fact that the oil palm land has a high C-organic content and a moderate level of N-total content. The utilization of the land resources of the former gold mine, it is necessary to do land improvementsin terms of soil physically, chemically and biologically.